Homoseksual Dalam Tafsir Klasik dan Kontemporer - Mustaqim, Abdul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2003)
The Alqur'an states that there are two kinds of sexual orientation in the history of mankind: heterosexuality and homosexuality. Nevertheless, the Alqur'an only acknowledges marriages of the first kind. There are many verses that stress that finding a partner (always a partner of the opposite sex) represents sunnatullah. In addition, the Alqur'an also criticizes the homosexual acts of the people of Lut, who is later punished by God. In this article Abdul Mustaqim goes further to cite the views of some commentators that contrary to what some people believe, homosexual potential is about nurture and not nature.